COMMUNICATION EFFECTIVENESS OF SURABAYA CITY GOVERNMENT THROUGH TWITTER AND FACEBOOK - Saodatul Qhamariyah; Achmad Nurmandi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
Advances in information and communication technology encourage the government as a stakeholder to have social media accounts. Likewise, the community is also required to have social media as a means of communication. The importance of social media has a very significant impact, especially in the field of government, for example as a medium in conveying suggestions and complaints from the public to the government or vice versa. Twitter and Facebook are some of the social media that are very popular with Indonesians. Including the Surabaya City Government, to support and develop policy programs made, they use this social media tool as an effective medium of communication. The purpose of this study was to determine the level of effectiveness of Surabaya city government communication via Twitter and Facebook. The research method used is descriptive qualitative by utilizing the Nvivo application to process the data. In this study, there are several assessment indicators used as benchmarks, namely (1) Accuracy, (2) Creativity, (3) Activeness, (4) Interaction, (5) Transparency. From the research results, it is known that the effectiveness of communication via Twitter is better than Facebook in terms of accurate information, creativity, activeness, and transparency. Meanwhile, in terms of interaction, Facebook is higher. Therefore, the Government is required to be even more innovative in conveying information to the public, so that people have an interest in knowing information about government and policies that have been announced.